Guidance and Counseling Services in Nigerian Tertiary Institutions: Problems and Solutions - Owobamigbe Kate David; Lawal Adijat Ohunene; Ogunode Niyi Jacob (Researchparks Publishing, 2021)
The various regulatory agencies of higher institutions directed all tertiary institutions in Nigeria to established Guidance and Counseling units in their respective institutions with the objective of providing quality Guidance and Career services to students and staff within the institutions. Many of these Guidance and Career centres are faced with challenges preventing them from discharging their statutory functions. This article discussed the challenges preventing effective Guidance and Counseling Services in tertiary institutions in Nigeria. Inadequate funding, Shortage of Trained Guidance and Counsellors, Inadequate Infrastructural Facilities and Inadequate Guidance and Counseling Materials will be used as challenges preventing Effective Guidance and Counseling Services and Career Development in Tertiary Institutions in Nigeria. To address these problems, the paper hereby recommend: allocate fund to the centre, guidance and counselling services should be seen as integral part of educational programme, employ professional/trained counsellors, provide adequate infrastructural facilities and provision of counselling materials.